Analysis of Earthquake Intensity on Java Island Using K-Means Clustering and GeoMap - Galan Kristianto Anver; Sri Yulianto J. Prasetyo (Publikasi Indonesia, 2025)
Indonesia is the country with the second highest earthquake intensity in the world because Indonesia is passed by the confluence of 3 tectonic plates, namely: the Indo-Australian Plate, the Eurasian Plate, and the Pacific Plate. Earthquakes occur due to the movement of tectonic plates that move freely and interact with each other. The impact of the earthquake includes: Tsunami, collapsed buildings, fires, rock collapses, and ground cracks. The purpose of writing this study is to determine the intensity of earthquakes that occur on the island of Java using the K-Means Clustering method. The earthquake data used in this study uses magnitude, depth, and geographical location parameters obtained from existing data. The K-Means Clustering method is used to group earthquake data into several clusters based on their seismic characteristics. The result of this study is to identify seismic zones with similar earthquake intensity. From the results of the cluster obtained, it was used to make data visualization of areas with high earthquake intensity using GeoMap